Evaluation of shear bond strength of a polyacid modified composite resin used as orthodontic bonding material - Sangeetha Duraisamy; W S Manjula; L Muthusamy; G Vimala (Wolters Kluwer Medknow Publications, 2012)
Background: Incorporating fluoride in the orthodontic bonding resin to prevent demineralization around orthodontic brackets reduces the bond strength, which is critical in the clinical performance of the resin. Aim and Objective: The aim of the study is to evaluate the shear bond strength of a polyacid-modified composite resin and compare it with a conventional composite resin and a resin-modified glass ionomer cement and to evaluate the site of bond failure and the amount of adhesive remaining on the tooth surface after debonding. Materials and Methods: Brackets were bonded using the three orthodontic bonding agents to 120 human premolars embedded in self-cure acrylic blocks, and shear bond strength was evaluated using the Instron universal testing machine. The debonded bracket surfaces were examined with a stereomicroscope to evaluate the site of bond failure and the presence of residual adhesive. Results: Composite resin bonding material showed the maximum initial and final bond strength followed by the polyacid-modified composite resin and resin-modified glass ionomer cement. The mode of bond failure for the polyacid-modified composite was adhesive failure at bracket adhesive interface or cohesive failure. Conclusion: The polyacid-modified composite resin produced shear bond strength in vitro within the range that is considered in the literature to be adequate for routine clinical use. Further clinical research is recommended to validate this finding.